PENYIDIKAN KASUS TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN DI WILAYAH HUKUM POLSEK MEDAN BARU - Nasrun Pasaribu; Madiasa Ablisar; Mahmud Mulyadi; Edy Ikhsan (Universitas Sumatera Utara, 2017)
ABSTRACT Investigation is investigating a series of actions in terms and in the manner set forth in this law to search for and collect evidence with evidence that makes light of the crime that occurred and to find the suspect. One of the criminal offense of criminal disturbing the public lately is theft, one of which is theft by weighting. Criminal acts of theft with aggravating elements or in doctrine also often called or qualified theft, ie theft in the form of principal or ordinary theft coupled with aggravating elements. The purpose of this study to determine investigation of criminal cases of theft by weighting were conducted by police in Medan Baru police. The research problems are that how the implementation of the investigation of criminal offenses of theft by weighting in the jurisdiction of New Medan police? What are the factors inhibiting the investigation of the crime of theft by weighting in the jurisdiction of New Medan police? To answer these problems do research with normative juridical and sociological juridical. Source of research data is of primary legal materials, secondary law, and tertiary legal materials. The collection of data through primary data through field studies (field research) by interviewing informants namely Medan police chief and a New Investigator, and secondary data through library research (library research). Based on these results the investigation of cases of theft by weighting in the jurisdiction of the Police of Medan recently directed in accordance with the modus operandi committed by the suspect or offender is breaking the windshield, crack car tires, housebreaking / store, damaging the lock rail and use the keys T, using a false key, deprivation bag, bank ATM burglary. Factors that become an obstacle in the process of investigating the case of theft by weighting that barriers of law, resistance from law enforcement, and obstacles of legal culture. Police investigators are advised to continue a relationship of coordination with the public prosecutor, is not passive or wait and expected to be more proactive in order to resolve the criminal case of theft by weighting takes place quickly.